Faktor resiko kejadian anemia pada remaja putri di SMAN 2 Moro’o - Demitri, Athira; Waruwu, Dirman Wati; Nababan, Agnes Sry Vera; Purba, Tuty Hertaty (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Anaemia occurs when haemoglobin levels in the blood fall below the typical 12 g/dl. The lack of iron, folic acid, vitamin B12, or protein can cause anaemia. Anaemia is mainly caused by low erythrocyte production and bleeding. This study aims to determine the risk factors of anaemia among female adolescents at SMAN 2 Moro'o. This study employed observational analytics using a case-control design. The population of this study was female adolescents, with a sample size of 64 respondents consisting of a case group of 32 respondents and a control group of 32 respondents, sampled using random procedures with a simple random sampling approach. The data was analysed using univariate analysis and bivariate analysis using the chi-square test and odds ratio. The results showed that there was a risk of knowledge p-value = 0.020 and OR 4.048, iron intake p-value = 0.016 < 0.05 and OR 12.130, menstruation p-value = 0.045 < 0.05 and OR 3.215, and obedience Fe tablets consumption p-value = 0.000 < 0.05 and OR 93.000. This research concludes that knowledge, iron intake, menstruation, and obedience to Fe tablets consumption are the risk factors for anaemia among adolescent females at SMAN 2 Moro'o.